Integrating Web-Based IoT Learning Media to Enhance Critical Thinking and Problem-Solving Skills in Vocational Education - Fatma Sukmawati; Eka Budhi Santosa; Sari Trisnaningsih; Jovita Ridhani; Relly Prihatin (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2025)
The integration of Internet of Things (IoT) technology in vocational education is essential for preparing graduates to meet Industry 4.0 demands. Although digital learning technologies have been widely studied, empirical evidence on the effectiveness of web-based IoT learning media integrated with problem-based learning (PBL) in vocational contexts remains limited. This study examines the instructional impact of web-based IoT learning media on vocational students’ critical thinking and problem-solving skills. A quasi-experimental non-equivalent control group pretest–posttest design was employed involving 60 eleventh-grade Mechanical Engineering students (30 experimental, 30 control). The experimental group participated in PBL activities supported by a web-based IoT platform for eight weeks, while the control group received conventional instruction. Data were analyzed using Analysis of Covariance (ANCOVA) to compare posttest outcomes while controlling for initial differences in pretest scores. The results indicate statistically significant improvements in critical thinking and problem-solving skills among students in the experimental group compared to the control group (p < 0.05). The effect sizes indicate a strong instructional impact within the studied context, though findings should be interpreted cautiously given the sample size. Overall, this study provides empirical support for the pedagogical potential of web-based IoT learning media in fostering 21st-century competencies in vocational education.